The Effectiveness of Acceptance and Commitment Therapy on Psychological Distress and Regretting The Spouse Choice in Betrayed Women - Sepideh Haddadi; Ghodratollah Abbasi; Bahram Mirzaeian (روانشناسی و روانپزشکی شناخت, 2025)
Introduction: Infidelity is a traumatic event that has many psychological consequences, including psychological distress and regret about choosing a spouse. Aim: The purpose of this study was to determine the effectiveness of acceptance and commitment therapy on psychological distress and regretting of the spouse choice in betrayed women. Method: This study was a quasi-experimental research. The statistical population of this research included all the betrayed women who referred to the counseling centers in Tehran, 2022, Among them 32 people were selected by purposive sampling and were assigned in two experimental and control groups. The participants completed the questionnaires of psychological distress by Kessler et al. (2002) and regret of choosing a spouse Schwartz et al. (2002) in three times: pre-test, post-test and follow-up. Repeated measures analysis of variance, Benferoni post hoc test and SPSS-27 software were used to analyze the data. Result: the results of the study indicated that acceptance and commitment therapy had a significant effect on psychological distress and regret of choosing a spouse in both within and between group status (P<0.05). The effectiveness of this intervention was lasting in the follow-up phase. The effect size for psychological distress and regret of choosing a spouse were 0.44 and 0.24 respectively (P<0.05). Conclusion: Acceptance and commitment therapy reduce psychological distress and regretting the spouse choice in betrayed women. So, suggestting in the design of effective interventions for betrayed women, acceptance and commitment therapy can be used to reduce the psychological distress and regretting of the spouse choice.